Audit Quality and Company Size on Tax Avoidance: The Role of Independent Commissioners - Surya, Raja Adri Satriawan; Zarefar, Arumega; Mela, Nanda Fito; Nurfitriani, Nurfitriani; Hamid, M; Adiman, R Multi Konvokesen (Akuntansi & Ekonomika, 2026)
This study examines the effect of audit quality and firm size on tax avoidance, with independent commissioners as a moderating variable. Using 595 firm-year observations from 94 manufacturing companies listed on the Indonesia Stock Exchange during 2016–2023, this study applies pooled panel regression with year fixed effects and firm-level clustered robust standard errors. The results show that audit quality is negatively associated with the effective tax rate, indicating higher tax avoidance. Firm size has no significant direct effect. Independent commissioners significantly strengthen the monitoring role of audit quality, but do not convert firm size into stronger tax compliance. These findings suggest that governance mechanisms influence tax avoidance differently depending on whether they operate through external audit quality or firm complexity.